EVALUATION THE ANTIBACTERIAL ACTIVITY OF LAWSONIA INERMIS :IN VITRO STUDY - Al-kurashy, Hayder; Al-windy, Salah; Al-buhadilly, Ali (Iraqi Journal of Science, 2024)
Aqueous and alcoholic extracts of lawsonia inermis were tested for their antimicrobial activity ;four types of bacteria were selected these are Staphylococcus aureus;Escherichia coli;Enterococus faecalis and Pseudomonus aureginosa .Minimal Inhibitory Concentration(MIC) were determined for both aqueous and alcoholic extracts ; the aqueous exracts was more potent than alcoholic extract regarding MIC 8-64mg/ml and 32-64mg/ml for aqueous and alcoholic extracs respectively .All the selected bacteria showed clear sensitivity for those extracts except the Escherichia coli showed more and greater .The results revealed that aqueous extract of lawsonia inermis is more potent than alcoholic extract in their antibacterial activity and produced bacteriostatic effects so in this study we recommended the use of this plant for superficial skin infections caused by S. aureus;P.aeruginosa and E. faecalis